The THE INFLUENCE OF INFORMATION CLARITY AND ENGLISH USAGE ON FOREIGN TOURISTS' WAYFINDING IN REGENCY TOURISM VILLAGES - Dananjaya, Ahmad Ghazy (International Journal of Instructions and Language Studies, 2026)
As Indonesia promotes community-based tourism in its eastern frontier, the readiness of visual communication infrastructure in remote areas becomes a critical success factor. This study aims to empirically measure the influence of Information Clarity and Use of English on the Ease of Navigation for foreign tourists visiting tourism villages in Fakfak Regency, West Papua. The research locus focuses on four specific villages representing Geographical Clusters of varying development statuses: Kampung Ugar (Advanced), Maas (Advanced), Fior (Developing), and Patimburak (Pioneer). The study employs a quantitative approach with an explanatory survey design. Primary data were collected via paper-based questionnaires during the peak tourist season to a sample of 200 foreign tourists, selected through a combination of cluster and incidental sampling. Data analysis was performed using Multiple Linear Regression in SPSS. The results demonstrate that Information Clarity and the Use of English both significantly affect the Ease of Navigation, with English usage having a dominant influence. The study concludes that visual and linguistic infrastructure are foundational to spatial orientation, mitigating spatial anxiety in complex topographies. Practically, these findings imply an urgent need for local governments to standardize bilingual, high-visibility signage to match official tourism development classifications.